Carecterización morfológica de los principales hongos fitopatógenos en el cultivo de remolacha (beta vulgaris l.), parroquia San Buenaventura Cotopaxi.¨ 2014 - Anchatipan Villacis, Francisco Rubén (2015)
This research has as its main theme the morphological characterization of plant pathogenic fungi in the cultivation of beet (Beta vulgaris L.), in the area of San Buenaventura 2014. Same Cotopaxi held in the laboratory of the Technical University located in Cotopaxi Eloy Alfaro Parish, Canton Latacunga, Cotopaxi Province, which had as its main objective characterize morphologically the phytopathogenic fungus that causes most impact production in the cultivation of beet (Beta vulgaris L.), in the area of San Buenaventura, Canton Latacunga Cotopaxi province. The following specific objectives were to: determine the phytopathogenic fungus greatest impact on crop production. Identify signs and symptoms of the fungus with the greatest impact from beet (Beta vulgaris L.) in field. Macro and micro structures characterize the pathogen. Describe the life cycle of the pathogen in laboratory conditions. Develop a tutorial of the morphological characterization of the fungus under study.